Hybrid Threats and Grey Zone Conflict : the challenge to liberal democracies (New York: Oxford University Press, 2024)
"Geopolitical competition between liberal democracies and authoritarian States is one of the defining features of our age. Most of this competition takes place below the threshold of armed confrontation, using measures short of war. Relying on the notions of hybrid threats and grey zone conflict to help make sense of these developments, this book brings together thinkers from various disciplines and backgrounds to consider some of the most pressing legal and ethical questions that arise in this context. The volume offers readers an assessment of the key concepts, trends and dynamics as well as a detailed analysis of specific areas. Individual chapters explore to what extent the existing rules and institutions of international law remain suitable for containing contemporary forms of geopolitical rivalry, how the law itself serves as an instrument, domain and object of strategic contestation and what ethical principles might provide normative guidance to liberal democracies and inform the application of conventional legal categories. The contributions in the book reflect different perspectives and approaches, but share the common assumption that hybrid threats and grey zone conflict exploit the vulnerabilities of democratic nations and pose substantial challenges to the international legal system. By providing a systematic assessment of these challenges, the book contributes to a better understanding of the field and towards devising more effective responses to address the adverse effects that hybrid and grey zone conflict have on liberal democracies and on the international rule of law"--Provided by publisher.
Keywords: Legal Ethics; International Law. -- Political Aspects; National Security. -- Law and Legislation; Rule of Law; Democracy. -- Philosophy; Liberalism; Globalization. -- Political Aspects